Support- and meaning-focused coping as key factors for maintaining adult quality of life during the COVID-19 pandemic in Germany - Cohrdes, Caroline; Pryss, Rüdiger; Baumeister, Harald; Eicher, Sophie; Knoll, Nina; Hölling, Heike (Frontiers in Public Health, 2023)
Introduction During the COVID-19 pandemic, questions about both consequences and helpful strategies to maintain quality of life (QoL) have become increasingly important. Thus, the aim of this study was to investigate the distribution of coping factors during the COVID-19 pandemic, their associations with QoL and the moderating role of certain sociodemographic characteristics. Methods Analyses were based on cross-sectional self-reports from German adult participants (N = 2,137, 18–84 years, 52.1% female) of the CORONA HEALTH APP Study from July 2020 to July 2021. Multivariate regression analyses were used to predict (a) coping factors assessed with the Brief COPE and (b) QoL assessed with the WHOQOL-BREF while taking measurement time, central sociodemographic, and health characteristics into account. Results During the COVID-19 pandemic, German adults mostly pursued problem- and meaning-focused coping factors and showed a relatively good QoL [Mean values (M) from 57.2 to 73.6, standard deviations (SD) = 16.3−22.6], except for the social domain (M = 57.2, SD = 22.6), and with a decreasing trend over time (β from −0.06 to −0.11, ps < 0.01). Whereas, escape-avoidance coping was negatively related to all QoL domains (β = −0.35, p < 0.001 for psychological, β = −0.22, p < 0.001 for physical, β = −0.13, p = 0.045 for social, β = −0.49, p < 0.001 for environmental QoL), support- and meaning-focused coping showed positive associations with various QoL domains (β from 0.19 to 0.45, ps < 0.01). The results also suggested differences in the pursuit of coping factors as well as in the strength of associations with QoL by sociodemographic characteristics. Escape-avoidance-focused coping was negatively associated with QoL levels in older and less educated adults (simple slopes differed at ps < 0.001), in particular. Conclusions The results demonstrated what types of coping may be helpful to avoid QoL deterioration (i.e., support- and meaning-focused coping) and provide implications for future universal or targeted health promotion (i.e., older or less educated adults who lack social or instrumental support) and preparedness in the face of unknown challenging societal situations similar to that of the COVID-19 pandemic. Cross-sectional trends of enhanced use of escape-avoidance-focused coping and QoL deterioration point toward a need for increased attention from public health and policy.